PERBEDAAN UJI KORELASI PEARSON, SPEARMAN DAN KENDALL TAU DALAM MENGANALISIS KEJADIAN DIARE - Cici Apriza Yanti; Ilham Julian Akhri (Jurnal Endurance, 2021)
Diarrhea is one of the infectious diseases that are commonly found in the Selayo community, Solok Regency. The purpose of this study was to find out the analysis of Pearson correlation test, spearman, control of the incidence of diarrhea in the work area of the Selayo Community Health Center. This type of research is Analytical survey with cross sectional study design using a non-reactive approach. The study population was the entire population in Nagari Salayo of 43,043 people from 22 jorong. Diarrhea incidence samples> 20 years old. Analysis using univariate and Bivariate analysis is then interpreted. The results showed that there was 0,000 food hygiene, sanitation sewerage 0.002, healthy house p-value 0,128 and toilet p-value 0,004 so it was small than alpha 0.05 then Ho was rejected Ha was accepted, meaning that there was a connection between the occurrence of diarrhea in the work area. Selayo Community Health Center. While the amount of alpha 0.05, then Ho was accepted by Ha was rejected, meaning that there was no correlation between the occurrence of diarrhea in the work area of the Selayo Puskesmas. It is hoped that researchers will be more careful in determining the appropriate statistical methods in testing hypotheses. If the data is interval or ratio scale, it is recommended to use the parametric method. Meanwhile, of the three tests, it turns out that the Pearson regression test was the highest in analyzing the strength of the relationship between the Independent and Dependent Variables